Addressing negative affect in substance use relapse prevention. Issue 1 (2nd January 2016) - Olsson, Kurt L.; Cooper, R. Lyle; Nugent, William R.; Reid, Rory C.
ABSTRACT: This review includes 15 studies, evaluating evidence of the effectiveness of interventions addressing negative affect in substance use relapse prevention. A unitary construct of "negative affect" was inadequate for reconciling conflicting findings. Instead, affect variables were divided by temporal range, model of affect, and discreteness of measurement. Results strongly support (1) cognitive behavioral therapy's effectiveness for changing tonic affect and (2) mindfulness interventions effectively changing both tonic and phasic affect. Evidence also supports mindfulness weakening the relationship between affect and substance use outcomes. Recommendations for future research are made.